Response of Grindelia camporum to P-amendment and VAM Inoculation in a Gomti Entisol - Mehrotra, N K; Ansari, S R; Maurya, K K (Annals of Arid Zone, 2016)
Grindelia camporum plants were grown at 5 graded levels of applied P, with and without Glomus fasciculawm and Scutellospora callospora inoculation, in a Gomti entisol. YAM improved plant growth in terms of height, average leaf area and the shoot biomass. At 50 mg kg-1 P205. VAM largely annuled its adverse effect on capitula yield. which has maximum grindelane diterpenoids; it increased the total yield of grindelane diterpenoids, specially in its ethyl acetate extractable hydrocarbon fraction. The beneficial effects of YAM could he attributed to its effect on root growth, uptake and translocation of P in the plant system and on the resulting biomass.